From New Man to New Lad: The Myth of Masculinity in NCT 127’s 'Kick It' Music Video - Khamaduddin, Muhammad (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
K-pop has been promoting various mythical masculinities to global audience through the boybandsÃ¢â‚¬â„¢ performances, in which it interests a huge attention. This study uses qualitative approach to uncover the myths behind the representation of masculinity in NCT 127Ã¢â‚¬â„¢s Ã¢â‚¬Å“Kick ItÃ¢â‚¬Â music video which was released in 2020. BeynonÃ¢â‚¬â„¢s classification of masculinity in media (New Man and New Lad) is used to classify the masculinity depicted in the music video. Moreover, BarthesÃ¢â‚¬â„¢ semiological model is employed to explore the denotation, the connotation, and the myth of the music video. Furthermore, the author captures five representative scenes to be analyzed. This study shows that the depictions of masculinity in the music video are varied. Mostly, the music video displays New Lad masculinity, but some scenes also depict New Man masculinity, or even the combination of both (hydra masculinity). Moreover, the uncovered myths in the music video are basically about the relationships between masculinity, violence, sport, and consumerism.